Secondary Traumatic Stress and Help-Seeking Behavior of Human Rights Officer: [Secondary Traumatic Stress dan Perilaku Mencari Bantuan Pada Human Rights Officer] - Tanlain, Eka Christiningsih; Sukmaningrum, Evi (Faculty of Psychology, Universitas Surabaya, 2023)
A human rights officer (HRO) is a human rights institution staff whose job is to receive and handle cases of alleged violations of human rights. They are at risk of experiencing secondary traumatic stress (STS) due to continuous exposure to cases of alleged violations of human rights. Left untreated, secondary traumatic stress (STS) will have an impact on the personal and professional life of the human rights officer (HRO). The qualitative-phenomenological analysis of the four human rights officers (HRO) in this study describes the secondary traumatic stress (STS) experienced and explores risk factors and help-seeking behavior which includes intentions and attitudes. The results of the study showed that the study participants showed symptoms of secondary traumatic stress (STS) in the High and Very High categories. This causes participants to become emotional, often think about work, and tend to avoid complainants. Physical reactions were also identified in human rights officers (HRO) who were still active in handling cases, such as getting tired quickly, falling asleep faster, and often having stomach ulcers. The risk factors for secondary traumatic stress (STS) for them are heavy workload, long working hours, increased frequency of case exposure and contact with complainants, handling of severe cases, complaining factors, lack of support from institutions and difficult to distance emotional involvement. All participants had the intention to seek help by informing third parties to receive support, solutions, and information when it became unbearable. Human rights officer (HRO) adalah staf lembaga hak asasi manusia (HAM) yang bertugas menerima dan menangani kasus dugaan pelanggaran hak asasi manusia (HAM). Mereka memiliki risiko mengalami secondary traumatic stress (STS) karena paparan kasus dugaan pelanggaran hak asasi manusia (HAM) yang terus-menerus. Secondary traumatic stress (STS) yang tidak ditangani akan berdampak pada kehidupan personal dan profesional dari human rights officer (HRO). Kajian kualitatif-fenomenologis pada empat human rights officer (HRO) dalam studi ini menggambarkan secondary traumatic stress (STS) yang dialami dan menggali faktor risiko serta perilaku mencari bantuan yang meliputi intensi dan sikap. Hasil studi menunjukkan bahwa para partisipan studi menunjukkan gejala secondary traumatic stress (STS) dalam kategori Tinggi dan Sangat Tinggi. Hal tersebut menyebabkan partisipan menjadi emosional, sering memikirkan pekerjaan, dan cenderung menghindari pengadu. Reaksi fisik juga teridentifikasi pada human rights officer (HRO) yang masih aktif menangani kasus, seperti cepat lelah, lebih cepat mengantuk, dan sering sakit maag. Faktor risiko penyebab secondary traumatic stress (STS) pada mereka adalah beban kerja yang berat, jam kerja yang panjang, peningkatan frekuensi paparan kasus dan kontak dengan pelapor, penanganan kasus yang berat, faktor pengadu, kurangnya dukungan dari institusi dan keterlibatan emosional yang sulit berjarak. Seluruh partisipan memiliki intensi untuk mencari bantuan dengan bercerita kepada pihak ketiga untuk mendapatkan dukungan, solusi, dan informasi jika sudah tidak tertahankan.